Constructive-geographic foundations of nature management on the north-western coast of the Black Sea - Pankratenkova, Daria Olegivna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
The aim of the research is to analyze the problem of anthropogenic influence on the sea coasts, to develop and improve the constructive-geographical foundations of rational nature management for the conservation and possible renewal of natural resources on the north-west coast of the Black Sea.Methods. The main methods used in the preparation process and writing of the article are systematization methods, retrospective, analytical, comparative geographical and historical.Scientific novelty of the article. The fact that the coastal zone of the Black Sea coast is experiencing uncontrolled anthropogenic impacts; this research has improved and developed constructive-geographical foundations for their rational management.Practical value. Developed scientific recommendations are universal. They are very important for the implementation of integrated management of the coastal zone in the country, the optimization of nature management and the preservation of the natural systems on the north-west coast of the Black Sea, in particular, and the entire World Ocean, as a whole.Research results. Intensive development of the coast and consumer economic activity over the past decades has led to the degradation of natural systems. Rational use of natural resources of the coastal zone of the sea assumed the development of foundations that comprehensively take into account the physical-geographical and socio-economic processes, as well as the laws of their development that determine the current state and dynamics of changes in natural systems during their operation. On the basis of a detailed study of domestic and foreign publications related to this topic, the activities of integrated coastal zone management (ICZM) in different countries of the world were analyzed. The foundations and principles for introducing ICZM in Ukraine are highlighted. It has been established that for the development of any projects in the coastal zone of the sea, it is necessary to have a scientific natural rationale from scientists obtained in the process of detailed research. These provisions can be the scientific basis of the relevant legislative framework for the optimization of nature management and spatial planning on the north-west coast of the Black Sea.Well-developed and improved scientific provisions are suitable for correcting the current situation in the direction of higher efficiency on coastаl control. These constructive-geographic foundations can become the basis and the main algorithm for practical implementation of environmental legislation in Ukraine.